Feasibility and reproducibility of spleen transient elastography and its role in combination with liver transient elastography for predicting the severity of chronic viral hepatitis. Issue 2 (5th June 2013) - Fraquelli, M.; Giunta, M.; Pozzi, R.; Rigamonti, C.; Della Valle, S.; Massironi, S.; Conti, C. B.; Aghemo, A.; Ronchi, G.; Iurlo, A.; Primignani, M.; Conte, D.; et al.
Summary Liver transient elastography (L‐TE) is a reliable, noninvasive predictor of disease severity in chronic liver disease of viral aetiology (CLD). Owing to the relationships among severity of CLD, portal hypertension and spleen involvement, the assessment of splenic stiffness (S‐TE) may have an added value in staging CLD. Of 132 CLD patients of viral aetiology, 48 with myeloproliferative disorders (MD) and 64 healthy volunteers (HV), were concurrently investigated by both L‐TE and S‐TE. Liver disease severity was staged by liver biopsy (LB; Metavir) taken concurrently with TE examination and upper gastrointestinal tract endoscopy for gastro‐oesophageal varices. The S‐TE inter‐observer agreement was analysed by an intra‐class correlation coefficient (ICC); L‐TE and S‐TE accuracy was evaluated by receiver operating characteristic (ROC) curve analysis. Logistic regression analysis assessed the independent effect of L‐TE and S‐TE as predictors of hepatic fibrosis stage. S‐TE failed in 22 CLD (16.6%), 12 (25%) MD and 12 (18%) HV. In the three groups, the ICC was 0.89 (0.84–0.92), 0.90 (0.85–0.94) and 0.86(0.80–0.91), respectively. In the CLD group, L‐TE and S‐TE independently predicted significant fibrosis (OR 5.2 and 4.6) and cirrhosis (OR 7.8 and 9.1), but at variance from L‐TE, S‐TE was independent from liver necroinflammation and steatosis. The NPV of S‐TE for gastro‐oesophageal varices was 100% using a 48 kPa cut‐off. In CLD, spleen stiffness alone or in combination with hepatic stiffness can be reliably and reproducibly assessed by TE with the added value of improving the noninvasive diagnosis of severe liver disease and excluding the presence of oesophageal varices.